Nonfunctioning adrenocortical carcinoma: a study of 12 cases - Ghanghoria, S; Raje, P; Jain, R; Ghanghoria, A (Journal of Pathology of Nepal, 2012)
Background: Adrenal cortical carcinoma is a rare malignant tumor. Several systems were proposed for diagnosis and evaluation of adrenocortical tumors.Weiss system is most commonly used method for assessment of malignancy, but only few studies has applied this criteria, for assesement of prognosis. The aim of this study was to analyzethe histological features & immunostaining status of adrenocortical carcinoma diagnosed according to Weiss criteria and correlate the data with patient clinical finding and outcomes. Materials and Methods: In this study clinicopathological features of 12 cases were reviewed and diagnosed as adrenocortical carcinoma on the basis of Weiss criteria and immunostaining. Grading was done according to the nine histopathological criteria of Weiss and is applied for assessment of prognosis. Each tumor was labeled malignant, when it scored ≥4 point of this histological criteria, tumors with ≤3 points were considered as adenoma and not included in the series. Immunostains applied were, Vimentin, Cytokeratin, synaptophysin, chromogranin, Vinyl mandilic acid, epithelial membrane antigen and Melan A. Results: All cases studied, presented at least four of the Weiss criteria and thus diagnosed as adrenocortical carcinoma. Patients with 7 and more score of Weiss criteria is considered as high grade carcinoma. Immunostains, have role in the diagnosis of adrenal cortical tumor, but does not have any significant clinical outcome. Conclusion: Weiss criteria was found to be a good prognostic factor in adrenal cortical carcinoma. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6020 JPN 2012; 2(3): 193-197